MASALAH-MASALAH PROGRAM POSBINDU DI DESA DAYEUHKOLOT KABUPATEN BANDUNG JAWA BARAT - Suparto, Tirta Adikusuma; Sunjaya, Deni Kurniadi; Susanti, Raini Diah (Universitas Pendidikan Indonesia, 2015)
Introduction: Integrated Development Post Program (Posbindu) is one of the facilities which provide a service for the elderly. Aside from healthcare, Posbindu also provides social, religion, education, skill, and other services. These services are needed by the elderly that makes Posbindu existence very important. According to the early researches conducted by the researcher in December 2013 at Posbindu’s Desa Dayeuhkolot, the implementations of Posbindu’s over there were still lacking. This study aimed to explore some issues of Posbindu programs in Desa Dayeuhkolot comprehensively. Method: The research design used in this research was kualitatif method approach by using case study. This research was conducted from February 2014 to January 2015 in 5 Posbindu. Result: The findings showed that the programs of Posbindu in Desa Dayeuhkolot Kabupaten Bandung still face some problems, they were: 1) Posbindu was not found based on people needs; 2) the lack of budget; 3) the lack of quality and quantity of guidance; 4) the lack of cadres’ knowledge and skills; 5) there was no incentive for cadres; 6) the lack of facilities and infrastructures; 7) the lack of emotional and physical test; 8) the lack of quality and quantity of health training program; 8) the lack of quality and quantity of health counseling ; 9) there was no access for medicine; 10) the complicated system of documentation and report ; 11) there was no elderly exercise in some posbindus; 12) the lack of effectiveness in elderly visitation program;13) the low frequency of elderly visitation; 14) the lack of posbindu contribution to the elderly; 15) the lack of support from the environment. Discussion: Posbindu’s revitalization was one of the interventions to solve the health problem caused by demographic changing. The Key point was to increase the capacity of cadre trough training.